Late Post Pancreatectomy Haemorrhage. Risk Factors and Modern Management - Sanjay, Pandanaboyana; Fawzi, Ali; Fulke, Jennifer L; Kulli, Christoph; Tait, Iain S; Zealley, Iain A; Polignano, Francesco M (JOP. Journal of the Pancreas, 2010)
Context Current management of late post-pancreatectomy haemorrhage in a university hospital. Objective Haemorrhage after pancreaticoduodenectomy is a serious complication. We report on risk factors and outcome following management by radiological intervention. Setting Tertiary care centre in Scotland. Subjects Sixty-seven consecutive patients who underwent pancreaticoduodenectomy. Methods All pancreaticoduodenectomies over a 3-year period were reviewed. International Study Group on Pancreatic Surgery (ISGPS) definition of post-pancreatectomy haemorrhage was used. Main outcome measures Endpoints were incidence of haemorrhage, pancreaticojejunal anastomosis leak, methicillin-resistant Staphylococcus aureus (MRSA) infection and mortality. Results Seven patients (10.4%) developed post-pancreatectomy haemorrhage out of 67 pancreaticoduodenectomies. Median age was 71 years. All post-pancreatectomy haemorrhage were late onset (median 23 days; range: 3-35 days), extraluminal and ISGPS grade C. Post-pancreatectomy haemorrhage arose from hepatic artery (n=4), superior mesenteric artery (n=1), jejunal artery (n=1), and splenic artery (n=1). Angiographic treatment was successful in all patients by embolisation (n=5) or stent grafting (n=2). Pancreatic fistula rate was similar in post-pancreatectomy haemorrhage and "no-haemorrhage" groups (57.1% vs. 40.0%; P=0.440); MRSA infection was significantly higher in post-pancreatectomy haemorrhage group (57.1% vs. 16.7%; P=0.030). Mortality from post-pancreatectomy haemorrhage despite successful haemostasis was 42.9%. Univariate and multivariate analysis identified MRSA infection as a risk factor for post-pancreatectomy haemorrhage. Conclusion CT angiogram followed by conventional catheter angiography is effective for treatment of late extraluminal post-pancreatectomy haemorrhage. MRSA infection in the abdominal drain fluid increases its risk and therefore aggressive treatment of MRSA and high index of suspicion are indicated. Image: Digitally subtracted angiographic image showing occlusive embolisation coils placed in the splenic artery.